Ketidakefektifan Hukum Untuk Pendatang Asal Luar Negeri Dalam Keimigrasian Di Wilayah Kota Bali - Felisha Aulia; Riau Wina Rachman; Ayu Efritadewi; Heni Widiyani (SYARIAH : Jurnal Ilmu Hukum, 2023)
This research examines the ineffectiveness of laws regarding immigrants from abroad in immigration in the Bali City area. Bali, as a major tourism destination, faces complex immigration problems involving visa misuse, overstay cases, and opening businesses without permits by foreigners. Law No. 6 of 2011 make Immigration is the focus of legal basis, but there are serious challenges in law enforcement and preventing immigration violations. This research uses a qualitative normative legal research approach with descriptive methods. Data were obtained from legal literature, immigration regulations, and immigration reports. The research results highlight immigration issues in Bali, such as cases of misuse of visas by foreigners from Russia and overstaying by foreigners from Nigeria. The ineffectiveness of laws regarding overstaying creates immigration uncertainty and vulnerability in the region. The research conclusions emphasize the need for increased supervision, consistent law enforcement, and education of immigrants regarding immigration regulations. Deportation sanctions are identified as an effective measure, but ongoing evaluation, capacity building of legal authorities, and cross-sector coordination are needed to increase the effectiveness of immigration law enforcement in Bali.